Transfusion-Associated Lyme Disease – Although Unlikely, It Is Still a Concern Worth Considering - Pavia, Charles S.; Plummer, Maria M. (Frontiers in Microbiology, 2018)
Hematogenous spread of the Lyme disease spirochete, Borrelia burgdorferi, has been well documented, yet there have been no reports (anecdotal or published) of transfusion-associated Lyme disease. Such a possibility would seem to exist but various factors, as discussed in this perspective, make this less likely to occur. Nonetheless, if not done already, safeguards need to be put in place at blood collection and dispensing facilities to ensure that the potential for the transfer of the Lyme disease spirochete through a blood transfusion remains a theoretical consideration rather than a real possibility.